Optimasi silase dengan aditif fermentasi dalam silo serta pengaruhnya terhadap organoleptik dan palatabilitas sapi perah - Salimah, Aldena Bina; Dwi Suharwanto; Didin Supriat Tasripin; Raden Febrianto Christi; Sari Suryanah, (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This study aimed to evaluate the effect of adding fermentation additives on the organoleptic quality and palatability of silo-fermented silage. Four treatments were tested in a completely randomized design: P1 (no additive), P2 (molasses), P3 (molasses + probiotics), and P4 (complete feed: molasses + probiotics + concentrate), each with six replications, and a palatability test involving five dairy cows. The silage was assessed based on organoleptic parameters and actual feed intake. The observed variables were organoleptic properties (aroma, smell, color, and texture) and palatability indicators (feeding duration and feed intake). The data obtained were analyzed using Analysis of Variance (ANOVA) followed by the Duncan Multiple Range Test (DMRT). The results indicated that the addition of fermentation additives did not have a significant effect (P>0.05) on aroma, texture, color, or palatability levels. These findings suggest that the forage quality and the fermentation conditions within the silo were optimal, resulting in no noticeable differences among treatments. The implications of this study highlight the need for further investigation into the dosage, composition, and forage characteristics of fermentation additives to achieve more distinct and applicable improvements in silage quality within dairy production systems